2017
DOI: 10.1128/aac.01957-16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vivo Efficacies of Tedizolid in Neutropenic versus Immunocompetent Murine Streptococcus pneumoniae Lung Infection Models

Abstract: Given that tedizolid exhibits substantial lung penetration, we hypothesize that it could achieve good efficacy against Streptococcus pneumoniae lung infections. We evaluated the pharmacodynamics of tedizolid for treatment of S. pneumoniae lung infections and compared the efficacies of tedizolid human-simulated epithelial lining fluid (ELF) exposures in immunocompetent and neutropenic murine lung infection models. ICR mice were rendered neutropenic via intraperitoneal cyclophosphamide injections and then inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In vitro studies in THP-1 macrophages demonstrated intracellular concentrations 10-to 15-fold higher than extracellular concentrations (22). However, a comparative study of tedizolid lung penetration in neutropenic and immunocompetent murine Streptococcus pneumoniae lung infection models demonstrated that the ELF penetration ratios were not significantly different between the two models (23). Therefore, the mechanism for the high ELF exposure is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies in THP-1 macrophages demonstrated intracellular concentrations 10-to 15-fold higher than extracellular concentrations (22). However, a comparative study of tedizolid lung penetration in neutropenic and immunocompetent murine Streptococcus pneumoniae lung infection models demonstrated that the ELF penetration ratios were not significantly different between the two models (23). Therefore, the mechanism for the high ELF exposure is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…12 The currently approved oxazolidinones (linezolid, tedizolid) exhibit in vitro bacteriostatic activities against staphylococci and enterococci, and bactericidal activities against streptococcal species. 11,[12][13][14][15][16][17] Of note, a greater intracellular accumulation 18 and at least 4-times greater in vitro potency of tedizolid compared with linezolid have been demonstrated in previous studies. 19,20 Furthermore, tedizolid has been described with a more favourable pharmacokinetic profile than linezolid in both Caucasian 21,22 and Asian healthy subjects.…”
Section: Introductionmentioning
confidence: 67%
“…10,11 The previous murine models of thigh infection or pneumonia established that both tedizolid and linezolid exhibit bacteriostatic activities against S. aureus regardless of methicillin resistance status [13][14][15]17 and bactericidal activities against S. pneumoniae, regardless of its penicillin susceptibility. 16 Although some discrepancy in the magnitude of the reduction of log CFU exists between studies which may be due to variation in the bacterial and/or mouse strains used or the initial bacterial load. 11,13,17 Additionally, a time-dependence in the time-kill activity has been shown in the study by Keel et al (2012) and by Xiao et al (2018), which suggest that tedizolid might have a greater anti-staphylococcal activity after exposure at 72 h than at 24 h. 13,17 The concentrations applied in this in vitro study represent those achieved with 200 mg once daily administration of tedizolid phosphate taking into account a protein binding of $87-90% for tedizolid.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, antimicrobial activity requires the achievement of sufficient drug levels at the site of infection. For pulmonary infections, assessment of ELF drug concentrations enables more robust predictions of the exposure-response relationships, compared with plasma concentrations (19)(20)(21)(22)(23)(24), but oftentimes data on the drug exposures at these critical sites are limited. In the present study, the availability of data on the meropenem-nacubactam bronchopulmonary pharmacokinetics in healthy adults provided the ability to evaluate the efficacy of the combination using the human-simulated ELF exposures in a murine lung infection model, which improves the translation application of the outcomes from this study to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported in vitro experiments demonstrated the activity of nacubactam in combination with either piperacillin, cefepime, or meropenem against a variety of ␤-lactamases, including CTX-M-15-and KPC-expressing Enterobacteriaceae strains (24,25). Additionally, the activity of nacubactam (previously OP0595) in combination with cefepime, as the ␤-lactam backbone, against CTX-M-15-positive E. coli (n ϭ 2) and KPC-positive K. pneumonia (n ϭ 2) isolates was evaluated by Morinaka et al in a thigh infection model (25).…”
Section: Discussionmentioning
confidence: 99%